Evaluation of the Characteristics of Three Kinds of Commercial Liquid Smokes and Its Application in the Processing of Smoked Loach - Meilan TIAN; Yangliu LIU; Aijin MA; Peiyu GAO; Yaxin SANG; Jilu SUN (Shipin gongye ke-ji)
In order to investigate the characteristics of different liquid smokes and their effects on the quality of smoked loach, the physicochemical properties, antioxidant capacity, antibacterial performance and polycyclic aromatic hydrocarbons (PAHs) content of three kinds of commercial liquid smokes were determined. The differences of volatile compounds in the three liquid smokes were analyzed by gas chromatography-ion mobility spectrometry (GC-IMS). The effects of different liquid smokes on the quality of smoked loach were investigated by color and sensory evaluation. Results showed that hardwood C-10-02 smoke liquid had the best overall performance, and its pH, phenolic compounds content and carbonyl compounds content were 2.38, 4.76 mg/mL and 3.35 g/100 mL, respectively. Its antioxidant capacity and antibacterial performance were also superior to the other two smoked liquids. Benzo[a]pyrene was not detected in the three kinds of smoke liquids, and the content of PAHs was well below the limit standards. A total of 58 volatile compounds were detected by GC-IMS, mainly including phenolic and carbonyl compounds. Partial least squares discrimination analysis (PLS-DA) combined with variable importance in projection (VIP) revealed significant differences in the volatile compounds in the three liquid smokes, and eight differential volatile compounds (VIP>1, P<0.05) were screened, namely 2-methoxy-4-methylphenol, 1-propanol, 3-hydroxy-2-butanone monomer, isobutyl alcohol dimer, butyraldehyde monomer, isobutyraldehyde monomer, 2,6-dimethoxyphenol and ethyl propionate. Besides, the optimal color parameters, flavor profiles, and textural characteristics were exhibited by smoked loach prepared with hardwood-derived C-10-02 liquid smoke. The highest overall acceptability was recorded for this formulation through organoleptic evaluation. The results of this study provide a theoretical reference for the production of liquid-smoked loach.